2014
DOI: 10.1128/jvi.01816-14
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Broadly Neutralizing Antibodies and Viral Coevolution in Two Subjects during the Early Stages of Infection with Human Immunodeficiency Virus Type 1

Abstract: Delineating the key early events that lead to the development of broadly neutralizing anti-HIV-1 antibodies during natural infection may help guide the development of immunogens and vaccine regimens to prevent HIV-1 infection. In this study, we monitored two HIV-1-positive subjects, VC20013 and VC10014, over the course of infection from before they developed broadly neutralizing antibody (bNAb) activity until several years after neutralizing breadth was detected in plasma. Both subjects developed bNAb activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 51 publications
3
74
0
Order By: Relevance
“…Using BLI, surface plasmon resonance, and ELISA, we previously showed that the soluble trimeric Env proteins used in this study as vaccines bind strongly to several potent bNmAbs that target conformational epitopes on the HIV-1 trimeric Env spike (22). The binding experiments also correlated well with neutralization of pseudoviruses expressing immunogens envs by neutralizing mAbs (NmAbs) (27). The gp140 Env trimer immunogens in these studies possess some but not all of the structural and antigenic components of native infectious virions.…”
Section: Rhesus Macaques Are Vaccinated With Dna + Protein Coimmunizamentioning
confidence: 71%
See 4 more Smart Citations
“…Using BLI, surface plasmon resonance, and ELISA, we previously showed that the soluble trimeric Env proteins used in this study as vaccines bind strongly to several potent bNmAbs that target conformational epitopes on the HIV-1 trimeric Env spike (22). The binding experiments also correlated well with neutralization of pseudoviruses expressing immunogens envs by neutralizing mAbs (NmAbs) (27). The gp140 Env trimer immunogens in these studies possess some but not all of the structural and antigenic components of native infectious virions.…”
Section: Rhesus Macaques Are Vaccinated With Dna + Protein Coimmunizamentioning
confidence: 71%
“…We have previously mapped bNAb activity of the human subject VC10014 to gp120 and the bNAb activity associated with VC20013 to the MPER of gp41 (27). Autologous anti-MPER NAbs were present during early infection (,1 y) and before heterologous neutralizing Abs (HNAbs) appeared in VC20013 (27).…”
Section: Macaque Abs Target Regions Of Env Associated With Autologousmentioning
confidence: 99%
See 3 more Smart Citations